Readiness Of Community Health Centers Nurse In Implementing Psychosocial Nursing Care During The COVID-19 Pandemic - Reni Nuryani; Sri Wulan Lindasari; Popi Sopiah; Hikmat Pramajati; Puspa Madya Nurhuda (Jurnal Keperawatan Muhammadiyah, 2023)
The COVID-19 pandemic has an impact on psychological changes: anxiety, depression, and fear which can cause psychosocial problems in the community. So, nurses are needed as holistic health care providers in carrying out psychosocial nursing care to help the recovery process of patients with psychosocial health problems during the COVID-19 pandemic as to reduce the risk of mental disorders. This study aims to determine the level of readiness of community health centers nurse in carrying out nursing care on psychosocial problems. This research uses quantitative descriptive research with a survey design. Respondents in this study were 105 health center nurses, using a simple random sampling technique. The descriptive data univariat analysis using SPSS Statistics 26 and the Behavioral Health Care Competency Survey instrument. The results showed that 57 respondents had high readiness (54.3%), 40 respondents had moderate readiness (38.1%), and as many as 8 respondents had low readiness (7.6%) in carrying out nursing care for psychosocial problems. Community Health Center nurses are ready to provide nursing care for psychosocial problems, as evidenced by the results of the nurse readiness survey at a high level. It shows that nurses can identify patients' psychosocial problems and provide appropriate interventions to people with psychosocial problems during the COVID-19 pandemic.